Genome-wide identification and expression analyses of the pectate lyase (PEL) gene family in cotton (Gossypium hirsutum L.) - Huiru Sun (BMC Genomics, 2018)
Abstract Background Pectin is a major component and structural polysaccharide of the primary cell walls and middle lamella of higher plants. Pectate lyase (PEL, EC 4.2.2.2), a cell wall modification enzyme, degrades de-esterified pectin for cell wall loosening, remodeling and rearrangement. Nevertheless, there have been few studies on PEL genes and no comprehensive analysis of the PEL gene family in cotton. Results We identified 53, 42 and 83 putative PEL genes in Gossypium raimondii (D5), Gossypium arboreum (A2), and Gossypium hirsutum (AD1), respectively. These PEL genes were classified into five subfamilies (I-V). Members from the same subfamilies showed relatively conserved gene structures, motifs and protein domains. An analysis of gene chromosomal locations and gene duplication revealed that segmental duplication likely contributed to the expansion of the GhPELs. The 2000 bp upstream sequences of all the GhPELs contained auxin response elements. A transcriptomic data analysis showed that 62 GhPELs were expressed in various tissues. Notably, most (29/32) GhPELs of subfamily IV were preferentially expressed in the stamen, and five GhPELs of subfamily V were prominently expressed at the fiber elongation stage. In addition, qRT-PCR analysis revealed the expression characteristics of 24 GhPELs in four pollen developmental stages and significantly different expression of some GhPELs between long- and short-fiber cultivars. Moreover, some members were responsive to IAA treatment. The results indicate that GhPELs play significant and functionally diverse roles in the development of different tissues. Conclusions In this study, we comprehensively analyzed PELs in G. hirsutum, providing a foundation to better understand the functions of GhPELs in different tissues and pathways, especially in pollen, fiber and the auxin signaling pathway.